Pragmatic Trials for Noncommunicable Diseases: Relieving Constraints. - Anushka Patel; Ruth Webster (PLoS Medicine, 2016)
In this month's editorial, PLOS Medicine Editorial Board member Anushka Patel and Ruth Webster discuss how applying rules for drug efficacy trials can impede pragmatic trials of interventions for noncommunicable diseases.